Rewriting Folklore Through Self-Narrative and Digital Content Creation Workshops among English Literature Students - Gigih Dwiananto; Iman Jauhari; Abd Ghofar (⁠International Journal of Asia Pacific Community Service, 2026)
This community engagement program aimed to enhance students’ understanding of digital folklore and encourage the reconstruction and expression of cultural identity through self-narrative practices and digital content creation. The program involved sixth-semester CWCU students of the English Literature Study Program from diverse cultural backgrounds. The implementation consisted of two main stages: a brief lecture on digital folklore and workshops on self-narrative and digital content creation. During the workshop sessions, participants were asked to write folktales originating from their respective regions and subsequently adapt them into social media content in visual and audio-visual formats. The results demonstrated that participants showed increased understanding of folklore transformation in the digital era and were able to reflect their cultural identities through creative social media-based practices. Furthermore, the program facilitated intercultural exchange among participants and improved digital literacy in the context of preserving local culture. Therefore, self-narrative-based digital folklore workshops can serve as a relevant educational strategy for integrating cultural preservation, digital creativity, and multicultural identity development within higher education contexts.